A physician‐initiated intervention to increase colorectal cancer screening in Chinese patients. Issue Volume 124:Issue S7(2018) (26th March 2018) - Sun, Angela; Tsoh, Janice Y.; Tong, Elisa K.; Cheng, Joyce; Chow, Edward A.; Stewart, Susan L.; Nguyen, Tung T.
Abstract : BACKGROUND: Among Chinese American individuals, only approximately 42% of cases of colorectal cancer (CRC) are diagnosed at an early stage, possibly because these patients are less likely than non‐Hispanic white individuals to undergo CRC screening. METHODS: Primary care physicians (PCPs) were recruited from a local independent practice association serving Chinese Americans and randomized into early‐intervention and delayed‐intervention groups. PCPs in the early‐intervention group received continuing medical education (CME), and their patients received an intervention mailer, consisting of a letter with the PCP's recommendation, a bilingual educational booklet, and a fecal occult blood test (FOBT) kit in year 1. PCPs in the delayed‐intervention group received no CME, and their patients received the mailers in year 2. RESULTS: A total of 20 PCPs were assigned to the early‐intervention and 22 PCPs to the delayed‐intervention group. A total of 3120 patients of these participating PCPs who had undergone CRC screening that was due during the study period were included. A total of 915 mailers were sent in year 1 and 830 mailers were sent in year 2. FOBT screening rates increased from 26.7% at baseline to 58.5% in year 1 in the early‐intervention group versus 19.6% at baseline to 22.2% in year 1 in the delayed‐intervention group ( P <.0001). The overall effect size of the mailer intervention with or without CME was estimated as a difference of 26.6 percentage points (95% confidence interval, 22.0‐31.2 percentage points) from baseline compared with usual care. The intervention was found to have no impact on rates of colonoscopy or sigmoidoscopy. CONCLUSIONS: The results of the current pilot study demonstrated that a mailer including educational materials and FOBT kits can increase CRC screening rates with or without CME for the PCPs. Cancer 2018;124:1568‐75 . © 2018 American Cancer Society . Abstract : Colorectal cancer is one of the most common cancers diagnosed among Chinese American individuals and physician involvement in health promotion can influence patients' health decision making and behavior. The physician‐initiated mailer intervention described in the current study significantly increases fecal occult blood test screening rates, but without the intervention, colorectal cancer screening rates are comparable to the rates observed at baseline.